PHOTOBIOREACTOR: TOOL FOR MASS CULTIVATION OF CYANOBACTERIA - Ramírez Mérida, Luis Guillermo (2014)
Cyanobacteria are efficient organisms in the conversion of solar energy and also produce a wide variety of metabolites. At the present time they are intensively used as biofertilizers, for the biofuel production, environmental pollution control as well as a nutrients source in human and animal food. With the aim to provide growth and use the cyanobacteria’s potential, efficient photobioreactors are required. Although many photobioreactor types have been proposed, just a few can be used for the biomass production of cyanobacteria. One of the main factors that limits the practical application of photobioreactors in biomass cultivation is mass transfer. Therefore understanding the mass transfer coefficient is of a great importance for efficient operation of the biomass cultivation in cyanobacteria. In this review, some very promising types of photobioreactors for cyanobacterial biomass production are discussed.